2012
DOI: 10.1177/1362361311435155
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of perceived negative impact in African American and Caucasian mothers of children with autism spectrum disorder

Abstract: The purpose of this study was to examine the stability of mothers' perceptions of the negative impact of having a child with ASD in a sample of African American and Caucasian families as their children transitioned to early adolescence. Participants were mothers and children participating in an ongoing longitudinal study of children referred for diagnosis of ASD at age two. Analyses included data from two time points, when child participants were approximately 9 and 14 years old. Linear mixed model analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Another possibility is that parents of different backgrounds self-refer for autism diagnosis at disparate rates. Carr and Lord (2013) found that African American mothers with lower education reported less negative impact related to having a child with ASD than Caucasian mothers. Feeling less caregiver burden may result in later diagnosis seeking by African American parents.…”
Section: Discussionmentioning
confidence: 95%
“…Another possibility is that parents of different backgrounds self-refer for autism diagnosis at disparate rates. Carr and Lord (2013) found that African American mothers with lower education reported less negative impact related to having a child with ASD than Caucasian mothers. Feeling less caregiver burden may result in later diagnosis seeking by African American parents.…”
Section: Discussionmentioning
confidence: 95%
“…To our knowledge, no studies have yet been conducted on ethnic differences in parent reporting on the BRIEF or the Vineland-II, outside of the standardization samples. However, some studies have also noted that Black mothers report lower perceived negative impact of having a child with ASD (Bishop et al 2007; Carr and Lord 2013). If parents do not experience symptoms of executive dysfunction, internalizing and externalizing behaviors, and adaptive deficits as problematic, they may be less likely to report their observation of these symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Yet the number and intensity of RRBs at age 2 was a unique contributor, besides IQ and social and communication deficits, to prediction of a stable autism diagnosis at ages 9 (Lord et al., 2006). Repetitive behaviors also contribute to parental stress, level of accommodations which parents are able to make (Carr & Lord, 2012) and academic achievement (Venter, Lord, & Schopler, 1992). Including RRBs in a diagnostic algorithm (Gotham et al., 2007) or in general screeners, such as the SRS, increases specificity considerably while changing sensitivity very little.…”
Section: Restricted Repetitive Behaviors and Interests As A Dimensionmentioning
confidence: 99%